The Position Of Sheikh Al-islam In Istanbul - بحيري يامنة (University of Eloued جامعة الوادي, 2024)
Through his Position, the Sheikh of Islam was able to play an important role during the various stages that the Ottoman Empire passed through, and his importance in this period is due to the many fatwas he issued on which the laws of the Ottoman Empire were based.This position had a significant impact on changing and developing several events, whether on the political side or in the field of public interest. It also played a major role in giving legitimacy to the laws issued, whether on political issues or matters related to the public interest.,Therefore, he played an important role in the political and religious fields were unique unprecedented in the Ottoman Empire. Was the status and the function of Sheikh alIslam one of the most important pillars forming the system of the Ottoman administration on which the Ottoman Sultanate relied?
Keywords: Sheikh of Islam; Ottoman Empire; Position; Important role; Istanbul